Ensuring food safety with molecularly imprinted polymers: innovative methods for the detection of aflatoxins in food and feed samples - Asghar Ali; Aqsa Sadiqa; Hamna Ilyas; Ayesha Bibi; Urvah Hussain; Naseer Iqbal; Adnan Mujahid; Adeel Afzal (Frontiers in Sustainable Food Systems, 2023)
Aflatoxins, a group of mycotoxins, represent a heterogeneous class of secondary metabolites that pose a significant risk to food safety and public health due to their potent toxicity. Aflatoxins are widely distributed in the environment, with high levels frequently observed in hot and humid conditions. There is an ongoing development of various methods for detecting aflatoxins in food and feed samples. Herein, a review of these methods is presented with special emphasis on molecularly imprinted polymers (MIPs) as selective materials for aflatoxins’ detection. The key findings of various methods for real-time analysis of food and feed samples are presented and analyzed, providing a comparative assessment of their performance. Furthermore, the challenges and limitations of these methods are discussed, considering their commercialization prospects and real-world requirements.